Pioneering the use of embedded research translation methodology for potential increased income and livelihoods of smallholder farmers - Kajobe, Robert; Kabuga, Experito Muyanja; Dricile, Ratib; Wadri, Victor; Malingumu, Richard; Yumbya, Peninah (Frontiers in Sustainable Food Systems, 2025)
Whereas participatory research and development is widely acclaimed, an effective explicit procedure for ensuring end-user participation remains a holy grail. Our study proposes a simple participatory approach by operationalizing the Embedded Research Translation (ERT), developed by LASER PULSE, and demonstrates its application among smallholder vegetable farming communities in the West Nile sub-region of Uganda. The ERT involves integrating research findings directly into practical applications or solutions within specific contexts. It emphasizes collaboration between researchers and stakeholders, ensuring that findings are relevant, actionable, and effectively applied in real-world scenarios. It is built on four pillars: (i) partnerships between researchers and stakeholders (ii) engaging in a process of generating a relevant research (iii) product and (iv) dissemination of findings. Based on these pillars and their underlying principles, an implementation process is recommended, beginning with a start-up stage where researchers actively involve a diverse range of partners and stakeholders. This is followed by a design stage, characterized by participatory discussions, collaborative decision-making, and planning. These steps guide the implementation phase, during which partners remain actively engaged in research. Finally, the partnership collectively disseminates the findings to maximize impact and uptake. In our study, we adapted the method to Ugandan context using a five-stage procedure: In the first stage (understanding the context), researchers rapidly obtain as much information as possible about the relevant aspects of the target cropping system and the broad areas of intervention through literature review, and quantitative baseline surveys. This is followed by the second stage (co validation) in which the information is validated by stakeholders through FGDs and feedback meetings. At the third stage (co-selection of priority areas of interventions), researchers and stakeholders co-select target crops and specific constraints to be addressed. The fourth stage is co-development which involves co-ideation and co-testing of potential technologies. The final stage (dissemination) consists of scaling the co-developed technologies through the partnership and other dissemination channels.